Hamamelis virginiana L. Leaf Extracts Inhibit the Growth of Antibiotic-Resistant Gram-Positive and Gram-Negative Bacteria - Matthew J. Cheesman; Sean R. Alcorn; Alan White; Ian E. Cock (MDPI AG, 2023)
Virginian witch hazel (WH; Hamamelis virginiana L.; family: Hamamelidaceae) is a North American plant that is used traditionally to treat a variety of ailments, including bacterial infections. Solvents of varying polarity (water, methanol, ethyl acetate, hexane and chloroform) were used to prepare extracts from this plant. Resuspensions of each extract in an aqueous solution were tested for growth-inhibitory activity against a panel of bacteria (including three antibiotic-resistant strains) using agar disc diffusion and broth microdilution assays. The ethyl acetate, hexane and chloroform extracts were completely ineffective. However, the water and methanolic extracts were good inhibitors of E. coli, ESBL E. coli, S. aureus, MRSA, K. pneumoniae and ESBL K. pneumoniae growth, with the methanolic extract generally displaying substantially greater potency than the other extracts. Combining the active extracts with selected conventional antibiotics potentiated the bacterial growth inhibition of some combinations, whilst other combinations remained non-interactive. No synergistic or antagonistic interactions were observed for any WH extracts/antibiotic combinations. Gas chromatography-mass spectrometry analysis of the extracts identified three molecules of interest that may contribute to the activities observed, including phthalane and two 1,3-dioxolane compounds. Putative modes of action of the active WH extracts and these molecules of interest are discussed herein.